P22 USE OF THE LIFE–VEST IN PATIENTS WITH HIGH ARRHYTHMIC RISK: EXPERIENCE OF A SPOKE CENTER IN THE COVID–19 PERIOD. (18th May 2022) - Corrado, L; Sena, L; Russo, M; Colangelo, G; Mazza, A; Riccio, G
Abstract: Background: Patients with newly found dilated heart disease have a high risk of sudden death. During the COVID period, the follow–up of these patients was difficult due to the limitation of access to the hospital and the impossibility of performing tests with high decision–making power (cardiac MRI) at third–level hospitals. Purpose: To evaluate the use of the Life–Vest in patients with newly found dilated heart disease as a protection system for early discharge and the related cost/benefit ratio in relation to an early ICD implant. Methods: In the COVID period, a Life–Vest was applied to 18 patients with newly found dilated heart disease (4 post ischemic and 16 without coronary artery disease), to monitoring ventricular arrhythmias and to protect them against any life–threatening ventricular tachycardias. These patients showed an high arrhythmic risk for ventricular tachycardias, (VT found on monitoring) and an unfavorable echocardiographic aspect. Each week, the patient's telemetry was remotely viewed and a telephone assessment was performed for clinical conditions. A control echocardiogram was performed at 30 days to evaluate the FE and the possible continuation of monitoring. Results: Of the 18 patients (mean age 59 years) analyzed, 5 (28%) underwent ICD implantation for persistent severe reduction in FE during 3 months after diagnosis and 13 (72%) normalized FE (duration average follow–up 50 days); there are no significant differences between the postischemic and non–postischemic DCM groups. The cost of renting the Life–Vest is about 4000 euros for 40 days and the average cost for an ICD implant, considering the device and the costs related to the days of hospitalization and use of human resources/advanced technological support, amounts to about 20700 euros. Considering these data, we observed a saving of approximately 261900 euros for 18 observed patients. To this saving must be added the costs related to the reduction of the days of hospitalization (average 5 days) and the costs to any future replacement of the ICD. Conclusion: In patients with newly found dilated heart disease at high arrhythmic risk, the use of the Life–Vest reduces the days of hospitalization, allows patients to be discharged safely and generates substantial savings for the National Health System.